The Religious Policy of the Soviet State and the Repression of Religious Scholars - Kalandarov Hamza Hamrokul ogli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article discusses the policy of repression carried out by the Soviet Union, including the repression of representatives of the religious sphere, Muslim scholars, and the fate of priests, mosques, and madrassas who became victims of the authoritarian regime.